Degradation-regulated architecture of injectable smart hydrogels enhances humoral immune response and potentiates antitumor activity in human lung carcinoma. (February 2020) - Duong, Huu Thuy Trang; Thambi, Thavasyappan; Yin, Yue; Kim, Seong Han; Nguyen, Thanh Loc; Phan, V.H. Giang; Kim, Jaeyun; Jeong, Ji Hoon; Lee, Doo Sung
Abstract: Cancer vaccines that elicit a robust and durable antitumor response show great promise in cancer immunotherapy. Nevertheless, low immunogenicity and weak immune response limit the application of cancer vaccines. To experience next generation cancer vaccines that elicit robust, durable, and anti-tumor T cell response, herein we design injectable smart hydrogels (ISHs) that self-assemble into a cellular microenvironment-like microporous network using a simple hypodermic needle injection, to localize the immune cells and program host cells. ISHs, composed of levodopa- and poly(ε-caprolactone- co -lactide)ester-functionalized hyaluronic acid (HA-PCLA), are loaded with immunomodulatory factor (OVA expressing plasmid, pOVA)-bearing nano-sized polyplexes and granulocyte-macrophage colony-stimulating factor (GM-CSF) as dendritic cell (DC) enhancement factor. Subcutaneous administration of ISHs effectively localized immune cells, and controlled the delivery of immunomodulatory factors to recruit immune cells. The microporous network allowed the recruitment of a substantial number of DCs, which was 6-fold higher than conventional PCLA counterpart. The locally released nano-sized polyplexes effectively internalized to DCs, resulting in the presentation of tumor-specific OVA epitope, and subsequent activation of CD4 + T cells and generation of OVA-specific serum antibody. By the controlled release of nano-sized polyplexes and GM-CSF through a single subcutaneous injection, the ISHs effectively eliminated B16/OVA melanoma tumors in mice. These ISHs can be administered using a minimal invasive technique that could bypass the need for extracorporeal training of cells ex vivo, and provide sustained release of cancer vaccines for immunomodulation. These important findings suggest that ISHs can serve as powerful biomaterials for cancer immunotherapy.